Evaluation of the Talking Library Department Service for Visually Impaired Users in National Library and the User Satisfaction Survey - Tezcan, Fatma Gamze; Tanrıkulu, Yüksel (Information World, 2011)
The purpose of this study is to evaluate the library services for the visually handicapped users by handling the “Talking Library” department in National Library and carry out a user satisfaction survey in respect of these evaluations. In this context, a questionnaire has been applied on November-December 2010 for visually handicapped users of National Library. A face to face interview was held with Altı Nokta Association of The Blind members, the staff of Rehabilitation Center for Visually handicapped, the students and teachers of Mitat Enç Visually Disabled Primary School, the students of Cumhuriyet High School and the visually disabled personnel of National Library and the other visually disabled users there, and some surveys were applied. Besides, the questionnaires were sent to the members of “Talking Library” department by e-mails via the personnel of “Talking Library” and answered. Totally 45 visually disabled people were mutually interviewed and among them 32 visually disabled users who have been using National Library Talking Library service or the ones used it before answered the questionnaire. By the findings obtained from the questionnaire, the user satisfaction has been assessed. The results of the questionnaire have revealed that the service for the visually disabled users in National Library Talking Library Department is not satisfactory and sufficient and some solutions have been offered within this scope.